Pemberian Molase Pada Aplikasi Probiotik Terhadap Kualitas Air, Pertumbuhan Dan Tingkat Kelangsungan Hidup Benih Ikan Mas (Cyprinus Carpio L.) - Dewi Sartika; Esti Harpeni; Rara Diantari (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
High concentration of ammonia is one of major problem in common carp (Cyprinus carpio) culture. It was caused by high stocking density and excessive feed. Molasses is biologicaly and economicaly considered as one of the safest way to increase the water quality. The aim of the research were to understand to effect of different molasses concentration which was applied in probiotic on the water quality, growth and survival rate of cammon carp. The research used five treatments namely (A) 0 g/Lmolasses, (B) 2,4 g/Lmolasses, (C) 4,8 g/Lmolasses, (D) 7,2g/Lmolasses, (E) 9,6 g/L molasses. Data of temperature, pH, DO and daily growth rate were analyzed by using Kruskal-Wallis nonparametric test, while the ammonia and survival rate were analyzed descriptively. The results showed that (1) molasses treatment on the application of probiotics provides influence on the afternoon temperature, pH and dissolved oxygen (DO) in the morning and afternoon, concentration of ammonia and survival rate (2) based on the stability of temperature, pH and DO in the morning and the afternoon, concentration of ammonia, growth and survival rate of carp higher than the other. The concentration of 2,4 g/L molasses was considered as the best treatment.